2017
DOI: 10.1038/srep43073
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Relationship between nanotopographical alignment and stem cell fate with live imaging and shape analysis

Abstract: Scientific Reports 6: Article number: 37909; published online: 02 December 2016; updated: 07 March 2017. The original version of this Article contained an error in the spelling of the author Jorge Luis Galeano Niño, which was incorrectly given as Jorge Luis Galenano-Niño. Additionally, there were typographical errors in Affiliation 9 which was incorrectly listed as ‘Sydney Medical School, The University of Sydney, NSW, 2006, Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In another study, substrates with aligned and random nanotopographies were fabricated by coating the surface of glass coverslips with carbon nanotubes (CNTs) (Figure 2B). [47] ASCs cultured on the aligned and random nanotopographies showed distinct differences in cell behavior. While the random topography caused cells to become more circular, the aligned topography caused cells to have an elongated shape that resulted in high expression of early stage markers of myogenic differentiation, suggesting commitment towards satellite cell muscle progenitors.…”
Section: Integrated Approaches To Bone Tissue Engineering Based On Biomimetic Designmentioning
confidence: 96%
See 2 more Smart Citations
“…In another study, substrates with aligned and random nanotopographies were fabricated by coating the surface of glass coverslips with carbon nanotubes (CNTs) (Figure 2B). [47] ASCs cultured on the aligned and random nanotopographies showed distinct differences in cell behavior. While the random topography caused cells to become more circular, the aligned topography caused cells to have an elongated shape that resulted in high expression of early stage markers of myogenic differentiation, suggesting commitment towards satellite cell muscle progenitors.…”
Section: Integrated Approaches To Bone Tissue Engineering Based On Biomimetic Designmentioning
confidence: 96%
“…Specifically, the osteogenesis or neurogenesis of hMSCs was enhanced by nanogrooves with a 1:3 spacing ratio rather than 1:1 or 1:5. In another study, substrates with aligned and random nanotopographies were fabricated by coating the surface of glass coverslips with carbon nanotubes (Figure B) . ASCs cultured on the aligned and random nanotopographies showed distinct differences in cell behavior.…”
Section: Recent Developments Toward Integrated Approaches In Bone Tis...mentioning
confidence: 99%
See 1 more Smart Citation
“…When BMSCs are seed on the aligned collagen coatings, the collagen nanofibers guide the cells to grow along the nanofiber direction to form elongated morphology (Figure ), with the afterward promoted cell adhesion, proliferation and differentiation, as well as mRNA expression of osteogenic markers (Figure ). As is well-known, cell spreading is partially guided by focal adhesions that form and distribute between cells and materials, mediated by integrins on the cell membrane . Previous studies have demonstrated that nanofiber alignment-induced formation of focal adhesion might mainly appear on the front edge of the elongated cells and parallel to the aligned nanofibers, which in turn resulted in the elongation of F-actin along the fiber direction, followed by the changes of genes transcriptions. , We therefore speculated the up-regulated osteogenic genes expression may be attributed to the alignment of the integrin-mediated actin elongation and arrangement.…”
Section: Discussionmentioning
confidence: 83%